A case of 'functional dysarthria' - Maya Devi (Journal of All India Institute of Speech and Hearing, 1970)
Miss S., aged 17 years reported to the clinic on 1-7-1971 with a complaint of speech defect. She developed the speech defect at the age of 9 years when she was operated for Osteomyletis. Her parents have not reported any other factor as the cause for her problem. Mothertongue of the case is Telugu, besides that she also can speak, read and write Kannada. She has studied upto IV standard and as she developed this speech defect, she discontinued her studies. She is the only daughter and there is no family history of speech and hearing defect or any other illness. No significant prenatal history is evident. Milestones of development are reported to be normal. Otolaryngological examination revealed normalfunctioning of the muscles of throat, larynx and palate. Audiological examination ievealed normal hearing. Psychological examination puts her on an 1 of 86(boarder-line intelligence). Neurological examination revealed normal reflexes and normal functioning of the cranial nerves and higher centres. This has indicatedfunctional liability in her. X-ray of the skull did not show anv abnormality. Hence she has been diagnosed as a case of 'Functional dysarthria.